A Nanostructured Cu(II) Coordination Polymer Based on Alanine as a Trifunctional Mimic Enzyme and Efficient Composite in the Detection of Sphingobacteria - Noelia Maldonado; Ana Latorre; Félix Zamora; Álvaro Somoza; Carlos J. Gómez-García; Agatha Bastida; Pilar Amo-Ochoa (Bioinorganic Chemistry and Applications)
This research raises the potential use of coordination polymers as new useful materials in two essential research fields, allowing the obtaining of a new multiartificial enzyme with the capacity to inhibit the growth of bacteria resistance. The fine selection of the ligands allows the design of a new 2D coordination polymer (CP), with the formula [Cu2(IBA)2(OH2)4]n·6nH2O, by the combination of Cu (II) as the metal center with a pseudoamino acid (H2IBA = isophthaloyl bis β-alanine). Quantitative total X-ray fluorescence (TXRF) analyses show that the obtained CP can gradually release Cu (II) ions. Additionally, this CP can be nanoprocessed and transformed into a metal-organic gel (MOG) by using different Cu (II) salt concentrations and the application of ultrasounds. Considering its nanometric dimensions, the slow Cu (II) release and its simple processability, its performance as an artificial enzyme, and its antibacterial ability were explored. The results obtained show the first nanocoordination polymer acting as an artificial multienzyme (peroxidase, catalase, and superoxodismutase) exhibiting antibacterial activity in the presence of hydrogen peroxide, with selective behavior for three bacterium strains (S. spiritovirum, A. faecales, and B. cereus). Indeed, this CP shows a more robust inhibition capacity for Sphingobacterium. Going beyond that, as there are no comfortable and practically clinical tests capable of detecting the presence of Sphingobacteria, the compound can be easily embedded to form moldable gelatin that will facilitate the handling and low-cost commercial kits.